ANALISIS KESTABILAN STATIK DAN DINAMIK PADA PESAWAT LSU-05 NG (LAPAN SURVEILLANCE UAV 05 NEW GENERATION) DENGAN MENGGUNAKAN PERANGKAT LUNAK XFLR5 - Zera Angeline Rerung; Edi Sofyan; Ferry Setiawan (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2020)
Aviation in Indonesia has progressed from time to time, both in terms of existing technology and infrastructure. One of them is the development of unmanned aircraft or commonly called unmanned aircraft which is commonly abbreviated as UAV (Unmanned Aerial Vehicle). The LSU-05NG aircraft is an unmanned aircraft designed by the LAPAN Aviation Technology Center (National Institute of Aviation and Space). This aircraft is designed to meet surveillance needs or is intended for observation of a very wide area of coverage only by installing sensor devices such as cameras and FLIR (Forward Looking Infra Red). To launch this surveillance mission, the LSU05NG aircraft must have stability. Due to the light weight and also small aircraft, the stability of this aircraft will be more easily disrupted, so there is a need for stability for the LSU-05NG aircraft to carry out its mission properly. An aircraft is said to be statically stable if the lateral dimension has a value ????ɩ???? < 0, the longitudinal dimension has a value ???????????? < 0, and on the directional dimension the value ???????????? > 0. By modeling the Lsu05 new generation aircraft and analyzing the stability of the aircraft in XFLR5 software so as to obtain the roots of aerodynamic characteristics. Based on the results of analyzes conducted on XFLR5 software, the LSU-05 new generation aircraft is statically stable and changes in speed cannot affect its stability.